# How do you solve #8 (4u - 1) - 12u = 11 (2u - 6)#?

##### 1 Answer

Sep 27, 2015

You would begin by distributing the term outside of you parentheses and then combining your like terms.

#### Explanation:

#8(4u-1)-12u=11(2u-6)# #8*4u# #8*-1# - Left side should now look like this:
#32u -8 -12u# - Right side:
#11*2u# #11*-6# - Right side should now look like this:
#22u-66# - Combine like terms and simplify:
#32u-8-12u=22u-66# #32u-12u=20u# #20u-8=22u-66# - Subtract
#22u# from both sides to combine and get#-2u# - Add
#66# to both sides so that way the#66# on the right side cancels out and you get#58# on the left side. - Final answer:
#-2u+58#